Isovolumetric Elasticity Alteration in the Human Heart Detected by InVivo Time-Harmonic Elastography - Tzschaetzsch, Heiko; Haettasch, Robert; Knebel, Fabian; Klaua, Robert; Schultz, Michael; Jenderka, Klaus-Vitold; Braun, Juergen; Sack, Ingolf (Ultrasound in Medicine and Biology, 2013)
Time harmonic elastography (THE) has recently been introduced for measurement of the periodic alteration in myocardial shear modulus based on externally induced low-frequency acoustic vibrations produced by a loudspeaker. In this study, we propose further developments of cardiac THE toward a clinical modality including integration of the vibration source into the patient bed and automated parameter extraction from harmonic shear wave amplitudes, wall motion profiles and synchronized electrocardiographic records. This method has enabled us to evaluate the delay between wall motion and wave amplitude alteration for the measurement of isovolumetric times of elasticity alteration during contraction (τC) and relaxation (τR) in a group of 32 healthy volunteers. On average, the wave amplitudes changed between systole and diastole by a factor of 1.7 ± 0.3, with a τC of 137 ± 61 ms and a τR of 68 ± 73 ms, which agrees with results obtained with the more time-consuming and expensive cardiac magnetic resonance elastography. Furthermore, because of the high sampling rate, elasto-morphometric parameters such as transition times and the area of wave amplitude-cardiac motion cycles can be processed in an automated way for the future clinical detection of myocardial relaxation abnormalities. © 2013 World Federation for Ultrasound in Medicine & Biology.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Cardiac elastography; Cardiac magnetic resonance elastography; Heart; Isovolumetric times; Shear modulus alteration; Time-harmonic shear waves